INSTALLATION FOR ORGANIZING EDUCATIONAL RESEARCH ON MECHANICAL OSCILLATIONS AND THE BREAKING EFFECT OF EDDY CURRENTS - Rybalko, Andrii (Physical and Mathematical Education, 2025)
Formulation of the problem. Educational experiments play a significant role in learning physics. They not only contribute to a deeper understanding of physical knowledge but also develop technical and mathematical literacy skills, which are especially important for engineering students. Therefore, organizing educational experimental research requires constant improvement in both material and methodological tools for their practical implementation. This article presents an installation that allows for organizing educational experimental research on mechanical oscillations of a physical pendulum and the braking effect of eddy currents. Materials and methods. Both theoretical and empirical methods were applied in the research. Specifically, an analysis of scientific publications was conducted, which reviewed educational experimental setups for studying oscillation damping and the braking effect of eddy currents in various mechanical systems. Additionally, the mathematical dependence of the braking force acting on a moving conductive plate in the magnetic field of an electromagnet on certain parameters was theoretically substantiated. Experimental verification of the theoretical calculations was performed. To practically implement the results of the author’s research, pedagogical observations of student activities were carried out during the testing of the proposed setup in the educational process. Results. A setup for graphically recording the oscillations of a physical pendulum and the braking effect of eddy currents was developed and practically tested. The obtained results confirmed the theoretical calculations of the dependence of the braking force acting on the moving conductive plate in the magnetic field on the square of the current strength in the electromagnet creating the field. An example of the results of an educational experiment was illustrated, and methodological recommendations were developed for possible directions of educational research in laboratory classes as well as during independent studies conducted by students (or pupils) under the guidance of an instructor. Conclusion. The proposed setup and recommendations for its application can be an effective didactic tool for teaching the sections "Electromagnetism" and "Oscillations." It can be used both as a demonstration experiment and in educational research of various formats (laboratory work, long-term student research, pupil research for the Junior Academy of Sciences competition, preparation of educational projects, etc.).